Sustainability of vegetable farming in Southern Mindanao, Philippines II. yield and profitability of growing six major crops - Rasco, E.T., Jr (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2005)
Vegetable crops were grown throughout the year in Kapatagan, Digos City, Davao del Sur Province in Southern Mindanao, Philippines based on data gathered from farmer interviews There was a wide range of yield and profitability in six major crops, reflecting the range of farming practices and cost of production, and the instability of prices of vegetables. Majority of the farmers obtained below average yield, and the average yields were generally less than 50% of the yields obtained in a comparable environment. Of critical importance in determining cost of production was interest payment on loan by 40% of the farmers, which ranged from 30-53% of cash expense. Interest payments accounted for the largest percentage of cost of production, followed by labor, fertilizers and pesticides (in that order). Highest aver- age net incomes were obtained from potato, cabbage and Chinese cabbage (PhP80799. PhP79203, PhP50287 per hectare, respectively). However, return on cash expense was highest for carrot at 3.68 per peso spent, followed by potato and cabbage with PhP3.58 and PhP2.55, respectively. In spite of these high returns, estimate of annual income from growing vegetable crops showed that 83% of the farmers earned less than PhP100,000 per year; 68% of them earned less than PhP50,000 per year. These earnings were barely sufficient to support their basic needs. Suggestions for improving vegetable farming and the overall economic condition of farmers in Kapatagan were offered.